2019
DOI: 10.1017/mor.2019.26
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting and Integrating the Contextual Influences of Ambiguities and Institutional Power in Organisational Research Design: A Case of Myanmar

Abstract: Our understanding of how an organisation operates is elucidated by the host country's political system. Myanmar has remained abstruse to researchers for many decades, as do most emerging markets prior to their transition from a centrally planned economy to a market economy such as China. We establish how the problematising and contextualisation of the methodologies adopted during longitudinal fieldwork in Myanma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Existing research findings could already be biased if reported data was accepted without its reliability being questioned. Win and Kofinas (2019) previously underscored the need for researchers to take into account the potential manipulation of reported data by financial institutions in emerging or developing economies, especially in governance research. Our critique of the dominant paradigms in corporate governance research is not an attempt to discredit these authors.…”
Section: Methodological Applicationmentioning
confidence: 99%
“…Existing research findings could already be biased if reported data was accepted without its reliability being questioned. Win and Kofinas (2019) previously underscored the need for researchers to take into account the potential manipulation of reported data by financial institutions in emerging or developing economies, especially in governance research. Our critique of the dominant paradigms in corporate governance research is not an attempt to discredit these authors.…”
Section: Methodological Applicationmentioning
confidence: 99%
“…This becomes a natural challenge for EM scholars to conduct interviews. Researchers can build trust from reflecting their roles in the research setting, employing a local interview assistant, and not recording and taking notes in the interviews (Win & Kofinas, 2019). Longitudinal data collection is also powerful in building trust and ensuring trustworthiness (Hota, Mitra, & Qureshi, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This helps to ensure contextually relevant data collection design and analysis, as well as an outsider's input that might uncover unrecognizable insights that are embedded in local context (Ratner, 1997). Some studies have proved to benefit from the researcher's ability to speak the local language without a foreign accent and in-depth knowledge in the local context (Liu et al, 2019; Outila, Piekkari, & Mihailova, 2019; Win & Kofinas, 2019). These advantages make the research focus on ‘contextual’ consistency rather than ‘verbal’ [literal] consistency (Xian, 2008: 235).…”
Section: Context and Methodology In Qualitative Scholarship In Ems: Rmentioning
confidence: 99%
See 2 more Smart Citations